A reversible near-infrared fluorescence probe for the monitoring of HSO3−/H2O2-regulated cycles in vivo. (4th October 2021) - Song, Qiuying; Zhou, Bo; Zhang, Dongyu; Chi, Haijun; Jia, Hongmin; Zhu, Peixun; Zhang, Zhiqiang; Meng, Qingtao; Zhang, Run
Abstract : A near-infrared (NIR) fluorescent probe (XC ) was constructed for the reversible detection of HSO3 − /H2 O2 in biosystems. The practical applications of XC were also demonstrated by the quantitative analysis of HSO3 − in white wine and sugar samples. Abstract : The development of well-designed fluorescence probes for the monitoring of redox homeostasis in biosystems has attracted significant research interest owing to their non-invasive and real-time detection capability in vivo . In this work, a reversible near-infrared (NIR) fluorescence probe (XC ) was designed and synthesized for the monitoring of HSO3 − /H2 O2 -regulated cycles in vivo . The XC probe contains a D–π–A–π–D conjugated structure with a reactive CC double bond in the benzopyrylium moiety. In the presence of HSO3 −, a nucleophilic addition reaction with the unsaturated carbon atom of XC occurred and rearranged the structure from the positively charged benzopyrylium moiety to neutral chromene. The HSO3 − -induced nucleophilic addition product (XC-SO3 ) can be oxidized to the native XC, resulting in the reversible responses to HSO3 − /H2 O2 cycles. In the presence of HSO3 −, XC presented a significant decrease in the absorption and emission spectra, as well as a solution colour change from blue to colourless under physiological conditions (pH = 7.4), which allows for the detection of HSO3 − by the "naked eye". By further incubation of XC-SO3 with H2 O2, the spectroscopic and colour signals were recovered. Biologically relevant species including anions, reactive oxygen species (ROS), biothiols and cations induced negligible spectroscopic responses. The detection limits of XC for HSO3 − and XC-SO3 for H2 O2 were calculated to be 1.02 μM and 0.84 μM, respectively. XC has several advantages such as high selectivity, reliability at physiological pH and low cytotoxicity, which enable its application in biological samples. Fluorescence imaging experiments in live adult zebrafish and live nude mice demonstrated that XC has the potential to monitor the HSO3 − /H2 O2 -regulated redox homeostasis in biosystems. The practical applications of XC were also demonstrated by the quantitative analysis of HSO3 − in white wine and sugar samples.